Pelatihan Capacity Building Bagi Perangkat Desa Kampung Baru dan Koto Sentajo Kabupaten Kuantan Singingi - Zulfan Saam; Thamrin Thamrin; Agus Mandar; Dhina Yuliana; Chitra Himawan; Melia Nurafni; Rosmayani Rosmayani (CANANG: Jurnal Pengabdian Masyarakat, 2024)
Capacity building can be done in two ways, namely through hard skills (work skills) and soft skills (personal and behavioral skills). Soft skills is a sociological term that refers to personality characteristics, social attractiveness, negotiation skills, personal habits, caring, and optimism. Soft Skills are personality and behavioral abilities and skills. These soft skills complement hard skills as technical requirements for a job. The objectives of the service activities that will be carried out include (a) providing understanding to village officials about the capacity building needed in community service and (b) providing skills in community service in the form of personal skills and behavior so as to improve the quality of community service. Village officials and other community servants have not been able to provide maximum services due to lack of discipline and responsibility, lack of cooperation both among officers and with the community. Village officials and other community servants such as posyandu officers, members of village PKK mobilizers, are officers who provide services to the community. Village officials and other community servants have not been able to provide maximum services due to lack of discipline and responsibility, lack of cooperation both among officers and with the community. This phenomenon is an indicator of a lack of ability or capacity as a public servant. Their main tasks and functions related to village government are quite well understood, but the supporting factors for their tasks which are directly related to their personal capacity as servants are still lacking. Capacity building through outbound activities is an outdoor activity which is training in the form of games to build personal abilities and behavior in improving the quality of service to the community. Capacity building activities can build aspects of personality and behavior of village officials as soft skills which are an inseparable part of basic skills in the form of basic tasks (hard skills) and functions as village government officials.